Impact of frailty status on medium-term follow up in patients undergoing percutaneous transcatheter aortic valve implantation in a high-flow referral center with high procedural volumes. (14th October 2021) - Fumagalli, C; Blandina, A; Nardi, G; Campicelli, S; Bandini, G; Marchetti, F; Demola, P; Meucci, F; Scheggi, V; Baldasseroni, S; Carrabba, N; Di Mario, C; et al.
Abstract: Background: Transcatheter strategies to treat aortic stenosis (AS) are an established therapeutic option in older patients not candidate for open heart surgery. Current guidelines recommend the adoption of surgical scores like the Society of Thoracic Surgeons (STS) as tools for risk stratification. However, these scores may have limited predictive value in older patients. Purpose: To assess the impact of frailty status on a composite endpoint comprising mortality and cardiovascular (CV) events in patients with severe AS evaluated for transcatheter aortic valve implantation (TAVI) in a high-flow and high-volume tertiary care center. Methods: Consecutive patients >80 years referred to TAVI from January to December 2019 at our tertiary care institution were prospectively screened for frailty through a comprehensive geriatric assessment (CGA) based on physical function and the Multidimensional Prognostic Index (MPI). Physical function was evaluated by the Short Physical Performance Battery (SPPB), a tool exploring balance, gait speed, strength and endurance that produces a score ranging from 0 to 12 (lowest to highest performance). The SPPB <6 is an established strong predictor of mortality and disability. The MPI is a three-level score used to stratify risk of mortality (low, intermediate or high risk) based on eight key domains for frailty assessment (functional and cognitive status, nutrition, mobility and risk of pressure sores, multimorbidity, polypharmacy and co-habitation). Data on mortality and CV events at 6 and 12 months were retrieved via administrative records and/or telephone follow-up. Results: Overall, 134 patients were referred for TAVI (mean age: 84±4 years; >90 years: 12%, women 67%). The average STS risk score was 4.6±3.0 (low risk: 49%; intermediate: 39%, high risk: 12%). Mean SPPB was 6.3±3.7 (SPPB <6: 32%). Ninety-five (71%) patients belonged to the MPI-low risk group, 30 (22%) to the MPI intermediate risk group and nine (7%) to the MPI high risk group. SPPB and MPI scores were moderately correlated with STS (Spearman correlation coefficient: SPPB R=0.31, p=0.01, MPI R=0.29, p=0.03, Figure Panel A and B). At 12 months, 3 (2.2%) patients died, and 11 (8.2%) were hospitalized for CV events: major bleeding, N=6 (4.5%); stroke: N=4 (3.0%); re-do: N=1 (0.7%). The probability of the composite endpoint was higher for patients at intermediate/high MPI risk (HR intermediate/high risk vs low risk: HR 2.9, 95% CI 1.1–6.8, p=0.031, Figure 1 Panel C), while no association with STS (p=0.332) was found. Conclusions: In a prospectively enrolled cohort of TAVI candidates, frailty indices stratified short- and medium-term prognosis. The integrated frailty assessment could be a useful tool for early detection of patients at risk of disability, and potentially, for preventing the futility of the TAVI procedure. Funding Acknowledgement: Type of funding sources: None.